Medicinal plants from the Himalayan region for potential novel antimicrobial and anti-inflammatory skin treatments. (22nd April 2021) - Heinrich, Michael; Jiang, Haiping; Scotti, Francesca; Booker, Anthony; Walt, Heinrich; Weckerle, Caroline; Maake, Caroline
Abstract: Background and Objectives: Adequate treatment of wounds remains one of the major medical needs globally, most notably in the regions with poor or limited access to health care. In many local and traditional systems of medicine, plants are often widely used for treating infected wounds. Aim and objectives: The overarching aim of this project was selection of potential species for use in a future treatment by combining with plant resources with aspects of antimicrobial photodynamic therapy (aPDT). Specifically, we focussed on species used locally in the Himalayan region for the treatment of skin disorders and then assessed the existing pharmacological evidence for key species based on the published evidence available. Methods: Database searches were performed to identify relevant publications describing local and traditional uses of plants in the Himalayan region of Bhutan, PR China, India, Nepal and Pakistan. Using the Global Biodiversity Information Facility (GBIF), species were researched in terms of their distribution including in different climatic regions, focussing on species mostly found in higher climatic zones (based on the Köppen–Geiger climate classification). For species used in three or more countries and restricted to the higher altitudes, data on safety, pharmacology, as it relates to dermatological conditions, and phytochemistry were retrieved. Key findings: The study identified a total of 606 species that are used in the treatment of various skin conditions often associated with infections reported in 84 articles. Common weeds like Ageratum conyzoides and Bidens pilosa, widely used and cultivated species like Centealla asiatiaca and Prunus armenica were excluded. This ultimately led to the identification of a core group of five widely used species restricted to the Himalayan region ( Cedrus deodara, Nardostachys jatamansi, Pinus wallichiana, Pinus roxburghii and Valeriana jatamansi ). Conclusions: Here we apply a novel approach comprising an assessment of the published information on the use of medicinal plants (i.e. local and traditional knowledge) in the context of their potential to be used in a biomedical form of clinical treatment – aPDT. Then, once sustainable sourcing based on access and benefit-sharing arrangements is in place, these species are investigated for their potential in wound treatment. Ultimately, the goal is to develop a new baseline for primary health care in some of the regions of the world with poor or limited access to health care.